2005
DOI: 10.1128/jcm.43.11.5775-5778.2005
|View full text |Cite
|
Sign up to set email alerts
|

New Quinolone Resistance Phenomenon in Salmonella enterica : Nalidixic Acid-Susceptible Isolates with Reduced Fluoroquinolone Susceptibility

Abstract: We describe the emergence of a new quinolone resistance pattern in Salmonella enterica isolates from Southeast Asia. These isolates are susceptible to nalidixic acid but exhibit reduced susceptibility to ciprofloxacin. The increase of such strains may threaten the value of the nalidixic acid disk test to screen for reduced fluoroquinolone susceptibility in salmonellas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…However, non-typhoidal Salmonella strains have been reported from southeast Asia that are susceptible to nalidixic acid but show reduced susceptibility to ciprofloxacin [11]. This phenomenon occludes the use of nalidixic acid resistance determination by the disk diffusion method as a tool to screen for decreased ciprofloxacin susceptibility in non-typhoidal Salmonella.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, non-typhoidal Salmonella strains have been reported from southeast Asia that are susceptible to nalidixic acid but show reduced susceptibility to ciprofloxacin [11]. This phenomenon occludes the use of nalidixic acid resistance determination by the disk diffusion method as a tool to screen for decreased ciprofloxacin susceptibility in non-typhoidal Salmonella.…”
Section: Resultsmentioning
confidence: 98%
“…This phenomenon occludes the use of nalidixic acid resistance determination by the disk diffusion method as a tool to screen for decreased ciprofloxacin susceptibility in non-typhoidal Salmonella. This resistance pattern may possibly be due to the presence of an efflux pump mechanism [12,13] or mutations at locations other than gyrA [11]. Fluoroquinolone resistance in non-typhoidal Salmonella has emerged as a threat to the health community in the past few years [14,15,16]; therefore, invasive infections with serious complication caused by non-typhoidal Salmonella should be treated with increased caution to avoid treatment failures [17].…”
Section: Resultsmentioning
confidence: 99%
“…Mutations at codon Ser83 or Asp87 are known to be common sites of mutation in gyrA, resulting in quinolone resistance (16,30), and all gyrA mutations detected in the present study (Asp87Tyr, Asp87Asn, and Ser83Phe) have been reported previously (14,16,41).…”
Section: Discussionmentioning
confidence: 62%
“…Studies have reported that since 2003 in Finland, NTS isolates with reduced susceptibility to fluoroquinolone (referring to ciprofloxacin MIC AE0.125 mg/mL), which were either susceptible or had only low-level resistance to nalidixic acid, had been isolated from Finnish travelers returning from Thailand or Malaysia (30,32,33). These isolates were referred to as the``nonclassical quinolone resistance phenotype'' (32,33), and isolates that were tested did not have a gyrA mutation (30,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation